2020
DOI: 10.1186/s12936-020-03510-3
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic analysis of the Plasmodium falciparum circumsporozoite protein in two distinct ecological regions in Ghana

Abstract: Background Extensive genetic diversity in the Plasmodium falciparum circumsporozoite protein (PfCSP) is a major contributing factor to the moderate efficacy of the RTS,S/AS01 vaccine. The transmission intensity and rates of recombination within and between populations influence the extent of its genetic diversity. Understanding the extent and dynamics of PfCSP genetic diversity in different transmission settings will help to interpret the results of current RTS,S efficacy and Phase IV implement… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 51 publications
4
9
0
Order By: Relevance
“…The current RTS,S, recombinant vaccine was constructed with pfcsp of P. falciparum 3D7 strain, but in Tanzanian isolates, only 0.7% 3D7-matched Tanzanian pfcsp haplotypes. Low matching of the 3D7 to the natural Pfcsp has been reported in many other studies in Africa (8,38,64,68). This data is consistent with other studies conducted across Africa and worldwide, which demonstrate low 3D7 haplotypes and little population structure.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The current RTS,S, recombinant vaccine was constructed with pfcsp of P. falciparum 3D7 strain, but in Tanzanian isolates, only 0.7% 3D7-matched Tanzanian pfcsp haplotypes. Low matching of the 3D7 to the natural Pfcsp has been reported in many other studies in Africa (8,38,64,68). This data is consistent with other studies conducted across Africa and worldwide, which demonstrate low 3D7 haplotypes and little population structure.…”
Section: Discussionsupporting
confidence: 91%
“…Similar findings were reported in Ghana where pfcsp sequences collected from two sites located over 784.4 km apart showed a largely homogeneous population with F ST below 0.05, and without any population structure as detected by PCA (62). This and other studies of the Pfcsp gene suggested a continued gene flow among parasites or human population mixing between the areas which might have contributed to the observed findings (62,64,65). High genetic diversity and a lack of population differentiation may have important implications related to the efficacy and emergence as well spread of vaccine-resistant parasites (66,67).…”
Section: Discussionsupporting
confidence: 88%
“…For natural selection of the C-terminal region, both Tajima's D and Fu and Li's D and F values were positive, indicating that the region may be experiencing positive selection, but these observations might be somewhat different from the study of Huang et al [ 20 ]. Some previous studies revealed that the C-terminal region might be in a state of balanced selection to maintain or produce the genetic diversity of the global PfCSP population, and the value of Tajima's D in other regions were positive and highly polymorphic, which might be due to the balanced selection of this immunogenic epitope by host immune pressure [ 35 37 ]. The Rm value of imported PfCSP in Henan Province was close to that in Africa, possibly because these were people returning from Africa.…”
Section: Discussionmentioning
confidence: 99%
“…The variant filtration steps were performed using VCFtools v 0.1.16 (Danecek et al 2011) and BCFtools v1.10.2 (Li 2011; Danecek et al 2021). The within-host infection complexity was assessed by calculating the F WS values (Amegashie et al 2020) with vcfdo (github.com/IDEELResearch/vcfdo; last accessed July 2022). An F WS threshold of >0.95 was used as a proxy for monoclonal infection.…”
Section: Methodsmentioning
confidence: 99%